SUSTAINABLE DEVELOPMENT AND IMPACT OF GLOBALIZATION ON TRIBAL AGRICULTURAL ENVIRONMENT OF EAST SINGHBHUM DISTRICT IN JHARKHAND - Mahali, Dr. Samu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Agricultural environment of tribes have own tradition and characteristics. They haveown genetically land ownership, sheds, pesticides, fertilizer, agricultural processes, agriculturalinstruments, agricultural byproducts and irrigation etc. Population growth and impact ofglobalization have changed the whole agriculture system of tribes during 1951-2011. Byproductof farmer like indigenous fishes, herbs, sheds (paddy),fertilizer are eroded and whole agriculturalland of this TD Blocks are converted as unfertile and fellow land due to miss use of chemicalpesticide and fertilizer. Marginal farmers have sold their bullock cart, bullocks and their landedproperty.Above genus agricultural and land use system before the development of industry in the studyarea:FOREST  / CULTIVATED LAND  SETTLEMENT AREA  CULTURAL ACTIVITIESAREA  RELIGIOUS LAND (Parle, 1992, p-408)CULTURAL ACTIVITIES AREA  RELIGIOUS LAND URBAN AREA (Parle, 1992, p408Above genus land use and agricultural system after the development of industry or impact ofglobalization in the study area: FOREST MINES / CULTIVATED LAND  INDUSTRIAL AREA SETTLEMENT AREA Process of rapid population growth started from the establishment of Tata Iron and SteelCompany in 1907 as well as copper mines at Mosaboni and Ghatshila in 1927. This developmentchanged the land use and agriculture system of tribes. Though their Living standard, Educationaland Economic condition had changed, they stand developed in all aspects but as a trade-off losttheir socio-cultural composition land use a great deal. They must continue their positivetraditional cultures and social traits and may do away with the negative sides like less